The Black man's burden : Africa and the curse of the nation-state - Davidson, Basil, 1914-2010. (New York : Times Books, 1992)
Basil Davidson is among the most widely read and respected of Africa's historians, and is, as Roland Oliver, author of The Cambridge History of Africa, has observed, "the one best trusted in Black Africa itself." Now, in this often brilliant, unfailingly provocative work, he traces the roots of Africa's independence movement and puts the continent's present-day political instability into historical perspective. Emerging from foreign rule in the 1950s, the African people looked hopefully toward a future of independence and self-determination. But today Africa is a continent in crisis. The root cause, argues Davidson, lies in a historical irony--Africa's liberators, reluctant to embrace Africa's own history, chose to form nation-states based on fundamentally flawed European models. Thus, the sectarian strife of Europe was reproduced in Africa, compromising the new nations almost from the moment of their birth. Filled with stimulating insights, The Black Man's Burden tackles some of the most vexing and fundamental questions of our time. Davidson begins with an inquiry into the pathology of nationalism and tribalism, and shows how they have collided in modern Africa. He demonstrates how the colonial legacy deformed (almost from the start) the project of African liberation. For African freedom fighters, mostly schooled in Western ways, could only imagine an African future inspired by the very West whose shackles they sought to break. Even the language of their discourse was derived from the West. Thus, they turned their backs on whatever might have proved useful and usable from their own African heritage. The creation of nation-states, like the Janus-faced nature of nationalism itself, proved, in the event, to be not so much liberating as suffocating. The state, Davidson argues, became a monster, its ever-inflating bureaucracy enrolled in the service of a particular family or ethnic group or tribe or alliance of tribes. Others, in an effort to resist the depredations of the state (or in a refusal to recognize its legitimacy), sought refuge in networks of tribal solidarity and community. Intelligent, passionate, sophisticated, Davidson explores the evolution of nationalism as it has unfolded in both Africa and Europe. He sheds light into obscure corners, combines scholarship with enthusiasm, and accomplishes that rare feat of turning the reader inside out in order to view the world with fresh eyes. He concludes with a reflection on movements of renewal and democracy that are now pushing their way across the continent.
Africa without history -- The road not taken -- Shadows of neglected ancestors -- Tribalism and the new nationalism -- The rise of the nation-state -- The challenge of nationalism -- The Black man's burden -- Pirates in power -- The European parallel.
Includes bibliographical references and index.
Keywords: Since 1960; Nation-state.; Estado nacional; Nation; nations; Ethnic relations; Nation-state.; Politics and government; Ethnische Beziehungen; 2; Nationalismus; 2; Nationalstaat; Stamm; Natievorming; Rassenverhoudingen; Intertribale betrekkingen; 2; Rassenbeziehung; Africa -- Politics and government -- 1960-; Africa -- Ethnic relations; Africa; Afrique -- Politique et gouvernement -- 1960-; Afrique -- Relations interethniques; Africa; Afrika; Afrika